Regulation of IkappaB Protein Expression by Early Gestation in the Thymus of Ewes - Yao Meng; Zhen Yang; Yaodong Quan; Shuxin Zhao; Leying Zhang; Ling Yang (Veterinary Sciences, 2023)
The thymus is an essential component of maternal immune systems that play key roles in recognizing the placenta as immunologically foreign. The inhibitor of the NF-κB (IκB) family has essential effects on the NF-κB pathway; however, it is unclear whether early pregnancy modulates the expression of the IκB family in the thymus. In this study, maternal thymuses were sampled on day 16 of nonpregnancy and different gestation stages in the ovine, and the expression of IκB proteins was analyzed. The data showed that B cell leukemia-3 and IκBβ increased; however, IκBα, IκBε, and IKKγ deceased during gestation. Furthermore, there was an increase in IκBNS and IκBζ expression values on day 13 of pregnancy; however, this decreased on day 25 of gestation. In summary, the expression of the IκB family was modulated in the thymus during early gestation, suggesting that the maternal thymus can be associated with maternal immunologic tolerance and pregnancy establishment in ewes.